Compounds of emerging concern as new plant stressors linked to water reuse and biosolid application in agriculture. Issue 3 (June 2021) - Mansilla, Sylvia; Portugal, José; Bayona, Josep M.; Matamoros, Victor; Leiva, Ana María; Vidal, Gladys; Piña, Benjamin
Abstract: Global crop production is limited by water, nitrogen, and phosphorous availability. Reclaimed water and organic fertilizers, such as crop residues, animal manure, and biosolids, can mitigate these needs. However, these materials may contain different pollutants arising from, among others, human and veterinarian health care, industry, cleaning media, or leakages from plastics or textiles. The European PRIMA-DSWAP project deals with the risks derived from these practices in relation to the presence of the so-called contaminants of emerging concern, or CECs, while exploring possible technical and mitigation measures to minimize those impacts. Risk assessment analyses of the CEC presence in soils and water bodies have been mainly focused in their consequences for human and environmental health, but very little has been studied about their potential negative effects on crop performance and quality. Here we review the current knowledge on macroscopic and molecular plant responses to the presence of several CECs known to abound in reclaimed waters, manure, and biosolids, with particular emphasis on crop plants, when available. With this information, and with the analysis of the potential implications of scaling these effects to the commercial agricultural level, we intend to contribute to the ongoing debate on the water reuse and biosolid application in agriculture in the context of circular economy. Graphical Abstract: ga1 Highlights: Use of reclaimed water and biosolids is becoming widespread in agriculture. The potential impact of this practice on crop performance is still poorly known. Current data on CEC plant toxicity indicates a potentially significant impact. Legal limitations for CECs levels in reclaimed water and amendments are proposed.